Enantioselective Allenylation of Aldehydes via Brønsted Acid Catalysis. Issue 23 (30th October 2018) - Wang, Mengzhou; Khan, Shahriar; Miliordos, Evangelos; Chen, Ming
Abstract: An enantioselective allenylation of aldehydes catalyzed by a chiral, nonracemic phosphoric acid was reported. Under the developed conditions, 1, 1′‐disubstituted allenic alcohols were obtained in 64–98% yields with 88–99% ee. Computational studies were conducted to probe the origin of asymmetric induction. Mechanistic studies suggest that the pinacol moiety of the propargylboronate is critical to the enantioselectivity of the reaction that was supported by experimental data. Abstract :